Anayasa mahkemesinin maddi ceza hukukuna ilişkin kararları üzerine bir inceleme - Çolak, Ali (My University, 2020)
Anayasa Mahkemesi’nin norm denetimi yoluyla maddi ceza hukukuna ilişkin verdiği birçok kararı bulunmaktadır. Bu kararlardan suç ve cezada kanunilik ilkesi ve ölçülülük ilkesi ile ilgili olanlar tezimizin konusunu oluşturmaktadır. İlk bölümde anayasanın üstünlüğü ve maddi ceza hukukuna dair verilmiş ve maddi ceza hukukunun temel ilkeleri açıklanmıştır. İkinci bölümde ise Anayasa Mahkemesi’nin norm denetimi yolu ile maddi ceza hukukuna ilişkin verdiği kararlar suç ve cezada kanunilik ilkesi ile ölçülülük ilkesine ilişkin açıklamalar yapıldıktan sonra ayrı başlıklar altında incelenmiştir. Bu inceleme sonucunda Anayasa Mahkemesi’nin bu ilkeleri ve bu ilkelerin alt ilkelerini nasıl yorumladığı, bu ilkelerden ne anladığı gibi sorulara yanıtlar aranmış, bu sorulara yanıt bulmak amacı ile Anayasa Mahkemesi’nin söz edilen kararları tek tek ve bir bütün halinde incelenerek Anayasa Mahkemesi’nin bu ilkelere maddi ceza hukuku bakımından nasıl yaklaştığı ortaya koyulmaya çalışılmıştır.

The Constitutional Court has many decisions regarding substantive criminal law through norm control. Among these decisions, the ones related to the legality principle of crimes and punishments and the principle of proportionality constitute the subject of this thesis. In the first part, general information as to the concept of the supremacy of the constitution and fundamental principles of the substansive criminal law were examined. In the second part of the study, the legality principle of crimes and punishments and the principle of proportionality were explained. Afterwards, the decisions of the Constitutional Court regarding the substantive criminal law through norm control were examined under separate titles. As a result of this examination, answers were sought to questions such as how the Constitutional Court interpreted these principles and sub-principles of these principles, and what it understood from these principles. In order to find answers to these questions, the mentioned decisions of the Constitutional Court were examined one by one and also as a whole, and it was revealed how the Constitutional Court approached these principles in terms of substantive criminal law.
Keywords: Anayasa mahkemeleri; Anayasa Mahkemesi kararları; Ceza Hukuku; Constitutional courts; Kamu hukuku; maddi cezahukuku; ölçülülük ilkesi Criminal law; Public law; substantive criminal law; suç ve cezada kanunilik ilkesi; the decisions of the Constitutional Law; the legality principle of crimesand punishments; the principle of proportionality; Turkey; Türkiye